Amplification and cloning the gene of bovine leukocyte α-A-interferon in cells of Escherichia Coli - Muttar, Arafat (Iraqi Journal of Science, 2023)
Interferon’s plays a role in innate immune responses through upregulation of costimulatory molecules and induction of proinflammatory cytokines. Interferon alpha (IFN α) type of Interferons. The present study characterized IFNα cDNA . The interferon’s play a great role in protection from infections, caused by microorganisms, and have powerful antiproliferative and immunomodulation activity. In this study DNA was isolated from bovine blood leukocyte, which was used in the quality of matrix for amplification of α-interferon gene with the use of PCR, and isolation of gene α-interferon and transformation in vector pUC18 and expression vector pET24b (+). All plasmids contained an additional DNA fragment size corresponding to the gene of bovine α-A-interferon.